The Impact of COVID-19 Pandemic on Teaching and Learning: A Case of the Schools Under Thrimshing Cluster, Trashigang - , Tsheten Tshering (Archives of Current Research International, 2022)
The purpose of this article was to study the impact of COVID-19 pandemic on teaching and learning of the students and teachers of schools under Thrimshing cluster, Trashigang Dzongkhag. The survey questionnaires was distributed to the teachers and students by surveyor. The data from the survey were analyzed by content analysis, percentage and descriptive statistics and qualitative data was analysed based on the themes. The findings indicated a mixed reactions. Majority of the teachers were positive with this mode of teaching while the students were at the receiving end. Most of the students suffered from numerous challenges of not having smart phones, internet connectivity and technical competencies to attend the online teaching and learning. Further, it has impacted their timely submission of assignments.